2012
DOI: 10.1074/jbc.m112.379552
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Fibrillation of the Destabilized Fourth Fasciclin-1 Domain Mutant A546T of the Transforming Growth Factor-β-induced Protein (TGFBIp) Occurs through Multiple Pathways with Different Oligomeric Intermediates

Abstract: Background: Corneal dystrophies are linked to aggregation of mutants of transforming growth factor ␤-induced Protein (TGFBIp) leading to blindness. Results: Depending on concentration, the fourth fasciclin-1 domain carrying the A546T substitution follows different fibrillation pathways involving different oligomeric intermediates. Conclusion: Aggregate species forming under different conditions have different biochemical properties. Significance: Understanding the molecular events causing aggregation is crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 65 publications
4
33
1
Order By: Relevance
“…However, we and other investigators showed that the disease-causing TGFBIp-mutants exhibit different stabilities and degradation pattern, which suggests that these factors are related to the disease mechanism 33–38 . We further showed that the LCD-associated mutant A546T displayed decreased thermodynamic and proteolytic stabilities compared with WT TGFBIp, but the GCD-associated mutation R555W stabilized TGFBIp 19, 31, 39 . Our previous data demonstrated that the stability and fibrillation propensity of the FAS1-4 domain were similar to full-length TGFBIp, which supports the use of FAS1-4 as a model system for TGFBIp fibrillation 19, 31 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, we and other investigators showed that the disease-causing TGFBIp-mutants exhibit different stabilities and degradation pattern, which suggests that these factors are related to the disease mechanism 33–38 . We further showed that the LCD-associated mutant A546T displayed decreased thermodynamic and proteolytic stabilities compared with WT TGFBIp, but the GCD-associated mutation R555W stabilized TGFBIp 19, 31, 39 . Our previous data demonstrated that the stability and fibrillation propensity of the FAS1-4 domain were similar to full-length TGFBIp, which supports the use of FAS1-4 as a model system for TGFBIp fibrillation 19, 31 .…”
Section: Discussionmentioning
confidence: 76%
“…We further showed that the LCD-associated mutant A546T displayed decreased thermodynamic and proteolytic stabilities compared with WT TGFBIp, but the GCD-associated mutation R555W stabilized TGFBIp 19, 31, 39 . Our previous data demonstrated that the stability and fibrillation propensity of the FAS1-4 domain were similar to full-length TGFBIp, which supports the use of FAS1-4 as a model system for TGFBIp fibrillation 19, 31 . The present study took advantage of this commonality and characterized the amyloid fibril core formed by A546T FAS1-4.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Samples were inspected in a JEOL 1010 transmission electron microscope at 60 keV. Images were obtained using an electron-sensitive Olympus KeenView CCD camera (33). Samples were recorded before and after incubation at 28°C for 30 min and 2, 4, and Ͼ45 h (45 h at 28°C followed by storage at 4°C for 4 days) with arbitrary magnifications of 25,000 (for samples after Ͼ45 h) and 40,000 (all other samples).…”
Section: Methodsmentioning
confidence: 99%
“…Several sheets usually associate with each other, forming large and sometimes twisted structures visible by microscopy techniques [22]. Early electron microscopy studies of amyloid fibrils tended to describe all amyloid using a single set of structural characteristics; however, there are some significant, albeit possibly superficial, differences between reported morphologies [21,[23][24][25]. The average length can vary from quite short (<100 nm) to very long (>1000 nm); in addition, the lateral association can be dramatically different, with some fibril types showing single fibrils whereas changing buffer conditions or protein type can lead to highly associated fibril structures.…”
Section: Mature Fibrilsmentioning
confidence: 99%